2021
DOI: 10.1002/trc2.12130
|View full text |Cite
|
Sign up to set email alerts
|

The association of circulating amylin with β‐amyloid in familial Alzheimer's disease

Abstract: Introduction:This study assessed the hypothesis that circulating human amylin (amyloid-forming) cross-seeds with amyloid beta (Aβ) in early Alzheimer's disease (AD).Methods: Evidence of amylin-AD pathology interaction was tested in brains of 31 familial AD mutation carriers and 20 cognitively unaffected individuals, in cerebrospinal fluid (CSF) (98 diseased and 117 control samples) and in genetic databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(75 citation statements)
references
References 31 publications
(89 reference statements)
4
50
0
Order By: Relevance
“…However, we found the presence of IAPP in brain sections from AD patients, but not that from non-AD subjects. This is consistent with the previous reports that IAPP is detected in the brain parenchyma and CSF of AD patients [ 32 , 33 ]. We detected no IAPP mRNA expression in the AD brain, suggesting IAPP in the brain is from the peripheral system.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, we found the presence of IAPP in brain sections from AD patients, but not that from non-AD subjects. This is consistent with the previous reports that IAPP is detected in the brain parenchyma and CSF of AD patients [ 32 , 33 ]. We detected no IAPP mRNA expression in the AD brain, suggesting IAPP in the brain is from the peripheral system.…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, compounds inhibiting the aggregation and/or stimulating the elimination of IAPP aggregates in T2DM may have the potential to treat AD [ 44 ]. Indeed, suppressing the secretion of amylin protected a rodent model against AD-associated phenotypes [ 33 ]. Moreover, treatment with the IAPP receptor antagonist has been shown to improve cognitive functions and reduce AD pathology in mouse models of AD [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, β-amyloid protein, tau protein, and amylin can interact synergistically, increasing to promote amyloid deposition, oxidative stress, mitochondrial dysfunction; inflammation, insulin resistance, and cell damage, culminating in dysregulation of amyloid metabolism, and glucose and neurodegeneration in AD and DM-2. In previous studies, it has been found that high plasma amylin concentration is associated with the incidence of AD, which suggests that amylin is a risk factor for AD[ 78 , 79 ]; and, amylin deposits in the brain have been found to interact with the β-amyloid protein and with tau protein in the pancreas and the hippocampus, which provides new evidence of a potential overlap between the understanding of the mechanisms of the pathophysiology of DM-2 and AD[ 80 ] (Figure 7 ).…”
Section: Amylin As a Link Between Dm-2 And Neurodegeneration: Admentioning
confidence: 99%
“…Cardiovascular complications affect around 65% of T2D patients despite medication and hIAPP aggregates mediates cardiotoxicity ( Despa et al, 2014 ; Rodriguez Camargo et al, 2018 ). Furthermore, T2D has been recognized as a risk factor for Alzheimer’s disease (AD) and cross-amyloid interactions between hIAPP and amyloid-β peptide (Aβ 1–42 ) have been shown to play a critical role in AD due to an increased toxicity of Aβ-IAPP hetero-oligomerization on neuronal cell membranes ( Roriz-Filho et al, 2009 ; Bharadwaj et al, 2020 ; Ly et al, 2021 ). A cross interaction between hIAPP and synuclein has been also suspected to also explain why patients with T2D are more likely to get Parkinson’s disease ( Horvath and Wittung-Stafshede, 2016 ).…”
Section: Introductionmentioning
confidence: 99%